Sistem Kendali Intensitas Cahaya dan Kelembaban Tanah untuk Umbi Porang (Amorphophallus Oncophyllus) menggunakan Metode Logika Fuzzy - Nur Syifa Syafaat; Hurriyatul Fitriyah; Edita Rosana Widasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Porang is a tuber that has high mineral and glucomannan content, of which glucomannan used for the pharmaceutical, beverage, cosmetic, adhesive/glue, and textile industries. In 2018, 254 tons of porang tubers were exported, with a value of Rp. 11.31 billion. Porang has its own growing requirements, including the height of the planting area between 100-600 masl, temperature 25-35 Â°C, loose soil texture with high organic content, good air aeration, neutral pH between 6-7, requires about 30% shade, and soil moisture of about 40%. Therefore, planting to harvesting porang tubers can only be done once a year, planting during the rainy season and harvesting during the dry season. Due to this, a control system is needed for light intensity and soil moisture so that the cultivation of this porang plant is more optimal. This system uses a BH1750 sensor which functions to measure light intensity and a soil moisture sensor to measure soil moisture in plants. This system uses Arduino UNO as a controller for controlling light intensity and soil moisture. In testing on the fuzzy logic method, soil moisture data has an accuracy of 70% and light intensity has an accuracy of 80%, and on average both have an accuracy of 75%. In 10 trials the average time required is 1.799 seconds..